Implementasi Soal-Soal Berstruktur Berbasis Information and Communication Technology (ICT) untuk Meningkatkan Aktivitas dan Hasil Belajar Biologi Siswa Kelas XI IPA1 SMA Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang - Muhiddin, Palennari; Maryam, . (Fakultas MIPA UNM, 2011)
This research was about the Classroom Action Research with the function for growing the activity and outcomes of learning through the ICT Questions Aplplications on learning biology. The Subject of this research was the student of class XI IPA1 SMA 1 Tellu Limpoe, the whole semester school year 2008/2009. It was about 31 students. The implementation of this research, there were two cycle. The data was getting trough 2 instruments, there were the data about the studentâ€™s activity during study process in the classroom which getting by sheet observation, and the data about the amount outcomes of learning. The data of studentâ€™s activity analyzed by qualitative analysis using the descriptive statistics. The amount of the analysis were: (1) outcomes of learning biology after the questions structural ICT in the first cycle in unsucces category are the score was about 66.32; the high score wasÂ 90.62 and the lower score 46.87 from the maximum score may be it can be reach 100; (2) In the second cycle it is in success category, it was about 73, 54 with the high score 91.43 and the lower score is 54.28 from the maximum score which may be can be reach 100. After that, it also expressed by the implementation-structured questions based on ICT, the disorder and belief in theirselves duringa the prosess of the study can be grown up.